2008
DOI: 10.1542/peds.2007-3016
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Cross-sectional Survey Study of the Natural History of Niemann-Pick Disease Type B

Abstract: Corresponding Author: Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
227
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(244 citation statements)
references
References 37 publications
11
227
1
5
Order By: Relevance
“…In contrast, type B patients have no overt signs of CNS involvement, but hepatosplenomegaly may be profound and accompanied by signs of liver failure [16][17][18]. Serum triglycerides and LDL-cholesterol are often elevated, while HDL-cholesterol is low.…”
Section: Clinical Features and Diagnostic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, type B patients have no overt signs of CNS involvement, but hepatosplenomegaly may be profound and accompanied by signs of liver failure [16][17][18]. Serum triglycerides and LDL-cholesterol are often elevated, while HDL-cholesterol is low.…”
Section: Clinical Features and Diagnostic Evaluationmentioning
confidence: 99%
“…Organomegaly can be significant, with an average splenic volume greater than ten multiples of normal [16][17][18]. Children with type B NPD often have growth restriction, particularly of linear growth, which is associated with a delayed bone age.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…10 Although there have been single case reports of deaths in patients with NP-B, to date there has been no systematic evaluation of the causes of mortality. In this article, we summarize the major morbidities in a series of 103 patients with NP-B who were evaluated at our center and describe the age and cause of death in 18 patients who died during the course of the study.…”
Section: Original Research Article © American College Of Medical Genementioning
confidence: 99%
“…4 NPD encompasses a broad spectrum of clinical phenotypes, ranging from a neuronopathic form with severe somatic disease, failure to thrive, and death during early childhood (NPD A) to a nonneuronopathic form with survival usually into adulthood and variable degrees of hepatosplenomegaly, cytopenias, interstitial lung disease, and dyslipidemia (NPD B). [5][6][7][8] No definitive disease-modifying treatment is available for ASMD despite attempts to use splenectomy, pulmonary lavage, liver transplantation, and hematopoietic stem cell transplantation. [9][10][11][12][13] Preclinical studies in an ASM knockout mouse model of NPD demonstrated that biweekly administration of olipudase alfa reduced tissue sphingomyelin concentrations in a dosedependent manner.…”
Section: Introductionmentioning
confidence: 99%